2015
DOI: 10.3892/ijmm.2015.2405
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal dielectric-barrier discharge plasma damages human keratinocytes by inducing oxidative stress

Abstract: The aim of this study was to identify the mechanisms through which dielectric-barrier discharge plasma damages human keratinocytes (HaCaT cells) through the induction of oxidative stress. For this purpose, the cells were exposed to surface dielectric-barrier discharge plasma in 70% oxygen and 30% argon. We noted that cell viability was decreased following exposure of the cells to plasma in a time-dependent manner, as shown by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. The levels of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
(33 reference statements)
1
24
0
Order By: Relevance
“…lipid membrane peroxidation, DNA breaks and protein carboxylation (19). These findings suggested that DBD plasma exerts cytotoxic effects via oxidative stress-induced damage to these components.…”
Section: Exposure Of Keratinocytes To Non-thermal Dielectric Barrier mentioning
confidence: 91%
See 1 more Smart Citation
“…lipid membrane peroxidation, DNA breaks and protein carboxylation (19). These findings suggested that DBD plasma exerts cytotoxic effects via oxidative stress-induced damage to these components.…”
Section: Exposure Of Keratinocytes To Non-thermal Dielectric Barrier mentioning
confidence: 91%
“…Cells were grown in Dulbecco's modified Eagle's medium (Thermo Fisher Scientific Inc., Waltham, MA, USA) containing 10% heat-inactivated fetal calf serum (Thermo Fisher Scientific Inc.), 100 µg/ml streptomycin and 100 U/ml penicillin. Non-thermal DBD plasma was applied as described previously (19). The cell suspension was adjusted to a concentration of 2x10 5 cells/ml and 11 ml was placed into 60 mm dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma treatment. Non-thermal DBD was used as the plasma source, as previously described (19). For DBD plasma treatment, cells were trypsinized and counted to adjust the density to 2x10 5 cells/ml, and 11 ml of cell suspension was placed in a 60-mm cell culture dish.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, we used a non-thermal dielecteic barrier discharge (DBD) plasma source with a gas consisting of 70% oxygen and 30% argon at atmospheric pressure. Previously, we showed that a DBD plasma system can generate ROS and induce apoptosis in human keratinocytes (19), and we used the same experimental settings for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma medical research inevitably involves experiments on reactive species because these were found to be central effectors in a number of biological targets exposed to plasma, such as skin cells [13][14][15], immune cells [16][17][18], and cancer cells . In many instances, hydrogen peroxide (H 2 O 2 ) was an important mediator in these in vitro experiments [53][54][55].…”
Section: Introductionmentioning
confidence: 99%